199 An Audit Cycle of Antibiotic Prophylaxis for Laparoscopic Cholecystectomy. (19th August 2022) - McMaster, D; Shaikh, M; Singh, S; Elghazaly, H; Dahaghin, P; Sheth, H
Abstract: Aim: Due to the lack of clinical benefit and the risks of unnecessary antimicrobial use, current national guidelines do not recommend prophylactic antibiotic use in low-risk elective laparoscopic cholecystectomies, reserving their use for high-risk patients only. The aim of this audit was to assess compliance with local and national guidelines for antibiotic usage for laparoscopic cholecystectomies, to identify areas of improvement, implement change and re-audit to assess the effectiveness of this change. Method: Data was collected retrospectively between 01/05/2021 and 01/08/2021 for patients undergoing elective laparoscopic cholecystectomies. Following the initial data collection, we implemented change by attaching pre-printed stickers of local antibiotic prophylaxis guidance to pre-operative notes. We prospectively re-audited between 01/11/21 and 01/12/21 to assess the effectiveness of this change. Results: In the initial three-month period, 24.4% (10/41) of elective cases received correct antibiotic prophylaxis, with 58.5% of patients prescribed unnecessary post-operative antibiotics in the post-operative plan. Following the implementation of change, in the re-audit period there was a significant improvement, with 55% (11/20) of elective cases receiving correct antibiotic prophylaxis, and only 25% prescribed unnecessary post-operative antibiotics. Conclusions: We show that pre-printed stickers are a simple intervention that can improve adherence to local guidance and reduce injudicious use of antibiotics in the pre- and post-operative periods. Improving antibiotic prescribing for laparoscopic cholecystectomies, one of the United Kingdom's most common surgical procedures, highlights the potential for significant cost savings and improved antimicrobial stewardship. We will re-audit again in the coming months to assess if this improvement has been sustained.